"After birth" abortion: a biomedical and conceptual nonsense. (July 2013) - Benagiano, Giuseppe; Landeweerd, Laurens; Brosens, Ivo
Abstract Recently, two authors suggested that killing a healthy newborn might be morally permissible, subsuming it under the heading of 'after birth abortion'. Their proposed new definition implies that infanticide should be permitted whenever II trimester abortion for social reasons is. The suggestion stirred public outcry; nonetheless it needs to be analyzed since some 20% of countries allow II trimester abortion for social reasons and 5% do this on demand. A proper delimitation of the definition of "abortion" is thus very important to ensure careful application; for this reason we have attempted a critical analysis of their arguments. In the area of pregnancy termination different moral standards are apparently applied in different countries, but many reasons exist why the equation between II trimester abortion for social reasons and the killing of healthy neonates is to be morally rejected in all cases. The "inversed reification" of the concept of infanticide as a more abstract, euphemistic 'after birth abortion' blurs the fundamental difference between a non-viable fetus and a viable neonate. The best-known and most widely utilized (although illegal) "social reason" for "late abortion" and "infanticide" is a pregnancy with a female fetus or neonate. If infanticide for neonates were to be considered morally permissible, specifically it is this practice that would be applied. And this should be rejected on two levels: conceptual, through a critique of the exclusive use of one specific notion of personhood, and pragmatic through refusal of gender-discriminatory forms of infanticide (the killing of female neonates). In conclusion, having investigated the new concept we have concluded that the term "after birth abortion" is biologically and conceptually nonsensical.